2013
DOI: 10.1371/journal.pntd.0002595
|View full text |Cite
|
Sign up to set email alerts
|

NLRP3 Inflammasome Activation by Paracoccidioides brasiliensis

Abstract: Paracoccidioides brasiliensis is the etiologic agent of paracoccidioidomycosis (PCM), the most prevalent systemic mycosis that is geographically confined to Latin America. The pro-inflammatory cytokine IL-1β that is mainly derived from the activation of the cytoplasmic multiprotein complex inflammasome is an essential host factor against opportunistic fungal infections; however, its role in infection with a primary fungal pathogen, such as P. brasiliensis, is not well understood. In this study, we found that m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
64
0
10

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(78 citation statements)
references
References 66 publications
4
64
0
10
Order By: Relevance
“…2C) is in accordance to the role of this receptor in the response against other fungal pathogens, as Candida albicans, 11 Aspergillus fumigatus, 16 Paracoccidioides brasiliensis 19 and dermatophytes as Trichophyton schoenleinii 18 and Microsporum canis. 17 However, the works on dermatophytes focused mainly on THP-1 monocytes, which show a constitutive caspase-1 activity and rely on pro-IL-1b transcription/expression as the limiting step for IL-1b production, while BMDMs obey to a 2-signal model to activate inflammasomes: signal 1, TLR activation for transcription; and signal 2, NLR activation for inflammasome assemblage.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…2C) is in accordance to the role of this receptor in the response against other fungal pathogens, as Candida albicans, 11 Aspergillus fumigatus, 16 Paracoccidioides brasiliensis 19 and dermatophytes as Trichophyton schoenleinii 18 and Microsporum canis. 17 However, the works on dermatophytes focused mainly on THP-1 monocytes, which show a constitutive caspase-1 activity and rely on pro-IL-1b transcription/expression as the limiting step for IL-1b production, while BMDMs obey to a 2-signal model to activate inflammasomes: signal 1, TLR activation for transcription; and signal 2, NLR activation for inflammasome assemblage.…”
Section: Discussionsupporting
confidence: 67%
“…IL-1b production relies on NLRP3, ASC and Caspase-1 Since the most studied inflammasome associated to fungal infections is the NLRP3, 11,[16][17][18][19] we sought to investigate whether this molecule could be necessary in our system. By analyzing the interaction between NLRP3 ¡/¡ BMDMs and T.rubrum conidia, we observed that the lack of this receptor did not change the interaction outcome ( Fig.…”
Section: Trubrum Conidia Induces Il-1b Production In Bmdmsmentioning
confidence: 99%
“…Tavares et al found that murine derived DCs released IL-1b in response to infection with the fungi, and released twice as much compared to macrophages. 104 The authors proposed that the fungus was specifically sensed by a nucleotide-binding oligomerization domain receptor (NLRP3) inflammasome, a cytoplasmic multi-protein complex that is dependent on a spleen tyrosine kinase, caspase-1, and NLRP3. When NLRP3 is activated, it recruits several peptides including pro-caspase-1 to form the NLRP3 inflammasome, activating caspase-1 and eventually leading to the cleaving of pro-IL-1b to IL-1b.…”
Section: Dendritic Cells In the Immune Responsementioning
confidence: 99%
“…The capacity of P. brasiliensis to activate the NLRP3 inflammasome are in agreement with previous studies using C. albicans, A. fumigatus and C. neoformans [105][106][107] and suggest that manipulating NLRP3 inflammasome activation may provide a new approach for the control of PCM. 104 Glycoprotein 43 (gp43) was first described in 1986, and it is the major diagnostic antigen of P. brasiliensis. 108 It stimulates an IFN-g dependent Th1 response that protects against infection by yeast forms of P. brasiliensis.…”
Section: Dendritic Cells In the Immune Responsementioning
confidence: 99%
“…Recently, it was suggested that P. brasiliensis induces Nlrp3 inflammasome-dependent IL-1b production (21). However, the signaling pathway, the mechanisms, and the role of the inflammasome in the control of this infection remain unknown.…”
mentioning
confidence: 99%